1995
DOI: 10.1177/0022022195263001
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Computers, Science, and Technology

Abstract: A comparative study of the structure of attitudes toward computers, science, and technology was carried out with 320 university students equally distributed by country (Italy and the United States), by field of study (humanities, psychology, science, and engineering), and by gender. The instrument used was a Likert-type scale of 56 statements. First, individual items were analyzed for cross-national differences. Then items showing a range of values within both national groups were analyzed by factor analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Females usually have a lower computer self-efficacy (Bandura, 1986;Compeau & Higgins, 1995;Divine & Wilson, 1997) than males, resulting in relatively fewer wishing to study Computer Science or I.S. Culture, race and first language are also often responsible for different attitudes to computing (Martin et al, 1992;Sacks, 1993;Busch, 1995;Sensales & Greenfield, 1995;Nielsen et al, 1997;Chrisholm et al, 1998;Gupta & Houtz, 2000). Prior experience of some sort with computers is usually a positive influence (Knezeck et al, 1993;Gos, 1996), and the maturity of students (Nielsen et al, 1997) can play a role.…”
Section: Prior Researchmentioning
confidence: 99%
“…Females usually have a lower computer self-efficacy (Bandura, 1986;Compeau & Higgins, 1995;Divine & Wilson, 1997) than males, resulting in relatively fewer wishing to study Computer Science or I.S. Culture, race and first language are also often responsible for different attitudes to computing (Martin et al, 1992;Sacks, 1993;Busch, 1995;Sensales & Greenfield, 1995;Nielsen et al, 1997;Chrisholm et al, 1998;Gupta & Houtz, 2000). Prior experience of some sort with computers is usually a positive influence (Knezeck et al, 1993;Gos, 1996), and the maturity of students (Nielsen et al, 1997) can play a role.…”
Section: Prior Researchmentioning
confidence: 99%
“…Age did not correlate significantly with ATEUI total score, nor did sex, a finding that contradicted earlier studies' findings of a higher level of anxiety or more negative attitudes among females (Dambrot et al, 1985;Darkenwald & Novak, 1997;Liaw, 2000;Liu & Reed, 1992;Popovich et al, 1987;Sensales & Greenfield, 1995;Young, 2000) and with one study that found females held a more positive attitude than did males ), but which agreed with others who found no gender difference (Behar & Hackett, 1991;Duggan et al, 2001;Duran, 2001;Heinssen et al, 1987;Jones, 1994;Kay, 1992;Loyd & Gressard, 1984b;Walters & Necessary, 1996).…”
Section: Resultscontrasting
confidence: 63%
“…Attitudes toward computers, science, and technology. Field of study and gender differences also were in evidence in a later study by Sensales and Greenfield (1995), but played a lesser role in attitude than other factors. A comparative study of the structure of attitudes toward computers, science, and technology was carried out with 320 university students equally distributed by country (Italy and the United States), by field of study (humanities, psychology, science, and engineering), and by gender.…”
Section: Sankaran Et Almentioning
confidence: 80%
See 2 more Smart Citations